Beginnings of the animated cartoon in the USA - Koupil, Vladimir (Aura musica, 2012)
The aim was to describe the beginnings of the animated cartoon in USA. The delineating of the term "comic strip". The familiarization with the personage Max Fleischer, in whose studio the involvement of songs to the process of animation was used for the first time. Other significant personality Walt Disney, the personage of the animated cartoon of the 2nd half of the 20th century. Carl Stalling's merit.
Keywords: Animated cartoon; Max Fleischer; songs